(untitled) (Journal of the College of Basic Education, 2023)
The activated carbon from seeds of dates was prepared by four methods: acid-treated, base-treated, steam-treated and heat-treated. All were compared with commercial activated carbon. The steam treated activated carbon has the highest surface area, and electrical conductivity, also the highest removal efficiency of Chemical oxygen demands (CODs) particles. Freundlich adsorption isotherms was used to analyze the adsorption efficiencies and the steam-treated carbon showed a higher adsorption capacity comparing to the commercial activated carbon. There is a great commercial potential to use dates’ seeds since they may be provide renewable raw materials that found in great abundance and the use of them to offer solution to the environmental problems and help the agricultural economy with an additional market potential.